Populations of Rumen Microbes and the In vitro Digestibility of Fermented Oil Palm Fronds in Combination with Tithonia (Tithonia diversifolia) and Elephant Grass (Pennisetum purpureum) - Jamarun, Novirman; Zain, Mardiati; Arief; Pazla, Roni (Pakistan Journal of Nutrition, 2017)
Objective: The aim of this research was to identify the rumen microbial populations and determine the in vitro nutrient digestibility of fermented oil palm fronds (FOPF) by Phanerochaete chrysosporium, which were supplemented with Ca, P and Mn minerals and combined with tithonia (Tithonia diversifolia) and elephant grass (Pennisetum purpureum). Methodology: This study used a randomized block design consisting of 4 treatment groups: T1 = 20% FOPF+80% (tithonia+elephant grass), T2 = 40% FOPF+60% (tithonia+elephant grass), T3 = 60% FOPF+40% (tithonia+elephant grass) and T4 = 80% FOPF+20% (tithonia+elephant grass). Four replicates were used per treatment. The ratio of tithonia to elephant grass was 1:4. Data were analyzed by analysis of variance (ANOVA) and differences among means were tested using Duncan’s multiple range tests (DMRT) with 5 and 1% confidence intervals. The measured variables were total bacteria, total protozoa, dry matter digestibility (DMD), organic matter digestibility (OMD) and crude fiber digestibility (CFD). Results: The results showed that total population of bacteria, DMD, OMD and CFD were the highest (p0.05). Conclusion: T1 (combination of 20% FOPF and 80% tithonia+elephant grass) had the best effect on rumen microbial populations and in vitro digestibility.